DO QUR’ANIC MORAL VALUES IN SURAH AL-HUJURAT (9–13) CHALLENGE MODERN ETHICS? - Salimudin; Shodiq, Muhammad; Ramadhani, Sitta; Nurhikmah; Putri, Nayla Damai Vadlina (SYAIKHONA: Jurnal Magister Pendidikan Agama Islam, 2026)
This study aims to enhance public understanding of the importance of moral education. Moral education serves as a fundamental foundation for individuals in practicing religious life. Moral teachings encourage individuals to consistently uphold good character and behavior, both in their relationship with God and in social interactions. The research employs a qualitative method through a literature study. Literature study involves a series of activities related to collecting data from written sources, reading, taking notes, and analyzing research materials. The primary source used in this study is Surah Al-Hujurat, verses 9 to 13, analyzed using the tahlili (analytical interpretation) method. The findings reveal that the moral education values contained in these verses include justice, brotherhood, respect for others, humanism, the prohibition of backbiting, and piety